Success Factors For The Implementation Of Public–private Partnerships In The Construction Industry In Uganda - Alinaitwe, Henry; Ayesiga, Robert (Penerbit Universiti Sains Malaysia, 2013)
With growing needs for infrastructure financing, many economies are turning to offbalance-sheet financing. In Uganda, for example, the ministry in charge of finance has been trying to find ways to implement projects funded using public–private partnership (PPP) arrangements. PPPs are risk-sharing investments in the provision of public goods and services, seen by governments as a means of launching investment programmes that would not be possible in reasonable amounts of time within the available public-sector budget. However, there has been no in-depth analysis of the factors that are likely to affect the success of PPP projects in developing countries. The objective of the present study is to address this gap and contribute to the knowledge base of success factors for PPP projects in developing countries, using Uganda as a base for data collection. Success factors were identified from the literature and validated using interviews with the three major types of stakeholders in the construction industry, i.e., contractors who represent the private sector and representatives of financial institutions and government departments, who are largely charged with the construction of public facilities. Using questionnaire surveys, the various factors were rated. The factors were then ranked in terms of the importance of the factors for each of the parties involved, using the coefficient of variation. A competitive procurement process, a wellorganised private sector, the availability of competent personnel to participate in PPP project implementation, and good governance are the most important cross-cutting factors identified.